Chapter Il tempo di Leonardo fra territorio e modernità - Pazzagli, Rossano (Territori, 2023)
Leonardo's life and work coincide with the time the modern world was born, involving a strong change in the relationship with the territory and an acceleration of human subjugation of nature. Leonardo's artistic and technical work moves between two polarities: the idea of a generating nature and the human aspiration to domination, with a vision of knowledge not yet fragmented by the specialism of modernity. Leonardo's multifaceted activity is a child of his age: of a Renaissance that was more innovation than method and of a period in which political transformations and a demographic recovery drew new attention to the territory.